The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1016/1010-7940(93)90063-h
|View full text |Cite
|
Sign up to set email alerts
|

Management of postoperative paralysis of diaphragm in infants and children

Abstract: During an 8-month period, 86 consecutive infants and children under 2 years of age underwent palliative or corrective cardiac surgery, of whom 11 subsequently developed phrenic nerve injury (PNI). This was seen most frequently following classic or modified Blalock-Taussig shunts. The diagnosis was established by ultrasound screening of the diaphragm, and patients were initially managed expectantly with ventilatory support. In nine patients no further management was necessary with demonstrated return of diaphra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 11 publications
3
27
0
Order By: Relevance
“…In our retrospective analyses the 5.4% incidence of DP after cardiac surgery is comparable to other retrospective studies that showed an incidence of 0.3-5.7% [3,[8][9][10]. In prospective studies the reported incidence varies from 0.5 up to 12.8% which may indicate a substantial number of undiagnosed patients or difficulties in diagnosis [3,9,11,12].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our retrospective analyses the 5.4% incidence of DP after cardiac surgery is comparable to other retrospective studies that showed an incidence of 0.3-5.7% [3,[8][9][10]. In prospective studies the reported incidence varies from 0.5 up to 12.8% which may indicate a substantial number of undiagnosed patients or difficulties in diagnosis [3,9,11,12].…”
Section: Discussionsupporting
confidence: 82%
“…In recent years an increasing number of phrenic nerve injuries associated with thoracic surgical procedures has been reported [4][5][6][7][8][9]. Today, it is the most common cause of DP in children with an incidence of 0.3-12.8% [3,5,10,11]. DP may present with respiratory distress, atelectasis, recurrent pneumonia or inability in weaning from ventilator.…”
Section: Introductionmentioning
confidence: 99%
“…Another important advantage of the laparoscopic approach is the option to avoid single-lung ventilation, which is always required with thoracoscopy. Postoperative ventilation time and outcome as reported here compare well with the literature [10,13,19,22]. Our patients remain free of respiratory dysfunction during a mean follow-up period of 7 years after surgery, which has also been confirmed by others [19,22].…”
Section: Surgical Techniquesupporting
confidence: 90%
“…These procedures sometimes require harvesting of autologous pericardium and/or wide exposure of the great vessels. Thymus resection for a clear surgical view, and exposure to the cold solutions have also been associated with phrenic injury [3,6,8,10,11,14,17]. The mean age of the patients who were plicated were found to be significantly young when compared with patients who did not undergo plication due to DP.…”
Section: Discussionmentioning
confidence: 99%
“…It is accepted that procedures in congenital cardiac surgery are the major causes of DP with an incidence ranging from 0.3 to 12.8% [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%